(untitled) (Revista de Ciências Agroveterinárias, 2021)
Heat waves have raised concerns about the damage they do to ecosystem services, and combined with droughts, excessive heat has favored the rise in tree mortality worldwide. Based on the hypothesis that the southwestern region of the state of Paraná presents suitable conditions for the occurrence of anomalous weather events characterized as summer heat waves, this study was conducted to observe air temperature patterns in the municipality of Dois Vizinhos between 2018 and 2020. Its specific objectives were to i) determine which periods of the day during the summer in Dois Vizinhos registered the highest air temperatures; ii) verify the events characterized as heat waves between the years 2018 and 2020 using the proposed forest-based stress index (FBS); iii) discuss the feasibility of the FBS index by making reference to other environmental monitoring indices; and iv) present arguments on aspects of ecophysiology and forest conservation. The results showed that the night period between 9 p.m. and 3 a.m. in Dois Vizinhos in summer 2020 was significantly hotter in the three years of the study. The interval between 3 p.m. and 9 p.m. in summer 2020 was significantly hotter among the hourly categories recorded. According to the FBS index, there were a total of 36 episodes characterized as Heat Waves in this region, including the nighttime.